An Assessment of Street Design With Universal Design Principles: Case in Aswan / As-Souq - Ahmed, Mai Eid Khalil; Sungur Ergenoglu, Asli (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2016)
The street is the backbone of the successful community. The design of an urban street should accommodate all people. This study focuses on the concept of Universal Design for streets and outdoor spaces. Besides, illustrates the basic considerations for urban street design. In the paper a case study, to examine urban public space, focusing on universal design is presented. The case study was conducted in AS-Souq street, Aswan, Egypt. For the case study, a descriptive research methodology was used. The field research encompassed: questionnaire as a quantitative technique and observations as qualitative strategies. A questionnaire was conducted in August 2015 with 330 respondents in total. The statistical analysis of survey questionnaire was achieved by using SPSS program. Discussing the findings of the case study is thought to lead a way to other public spaces specifically streets to be more inclusive in design. This study confirms that applying UD as a strategy ensures equal and democratic rights in society for all, consequently encouraging full participation in social life by ensuring access to and usability of all aspects of society, including the built environment, thus improving quality of lifein the urban fabric and the entire community.
Keywords: As-souq Street; public space; Universal Design Principles; Architecture